Research Trend of User-Generated Content in Tourism - Batara Nobon Siregar; Ari Sulistyanto; Hamida Syari Harahap; Wichitra Yasya; Dwinarko Dwinarko (Dinasti International Journal of Education Management And Social Science, 2024)
The habit of sharing travel experiences on social media is increasingly attached to modern life today, making the theme of User Generated Content (UGC) in tourism never be uninteresting topic to research. Research on UGC in tourism grew 30.31% over the last 10 years. This study uses a bibliometric approach to analyze the database from Scopus with the keyword "User Generated Content" AND Tourism, in the period 2014 – 2023. 504 documents were found from the database and use PRISMA to select, narrowing it down to 321 documents that were used as units of analysis. The application "Biblioshiny R package Bibliometrix" is used for data analysis and visualization. The results showed that the theme with “online”, “findings” and “reviews”, is still a research trend in the future.